2005
DOI: 10.1007/s10350-005-0055-3
|View full text |Cite
|
Sign up to set email alerts
|

Practice Parameters for the Treatment of Perianal Abscess and Fistula-in-Ano (Revised)

Abstract: The American Society of Colon and Rectal Surgeons is dedicated to assuring high-quality patient care by advancing the science, prevention, and management of disorders and diseases of the colon, rectum, and anus. The Standards Committee is composed of Society members who are chosen because they have demonstrated expertise in the specialty of colon and rectal surgery. This Committee was created to lead international efforts in defining quality care for conditions related to the colon, rectum, and anus. This is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
220
1
12

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(252 citation statements)
references
References 58 publications
3
220
1
12
Order By: Relevance
“…This conclusion is similar to the recommendations of the Association of Coloproctologists of Great Britain and Northern Ireland (ACPGBI) that a cutting seton should be used as the primary treatment only for a low transsphincteric fistula or as the secondary treatment for a low intrasphincteric fistula [24]. Whiteford et al [32] found that complex fistulas may be treated with a cutting seton. They defined a fistula as complex under the following circumstances: as complex primary track crossing 30-50% of the external sphincter (high-transsphincteric, suprasphincteric and extrasphincteric), anterior track in a female, multiple tracks, recurrent fistula, pre-existing incontinence, previous local irradiation, Crohn's disease.…”
Section: Referencesupporting
confidence: 79%
“…This conclusion is similar to the recommendations of the Association of Coloproctologists of Great Britain and Northern Ireland (ACPGBI) that a cutting seton should be used as the primary treatment only for a low transsphincteric fistula or as the secondary treatment for a low intrasphincteric fistula [24]. Whiteford et al [32] found that complex fistulas may be treated with a cutting seton. They defined a fistula as complex under the following circumstances: as complex primary track crossing 30-50% of the external sphincter (high-transsphincteric, suprasphincteric and extrasphincteric), anterior track in a female, multiple tracks, recurrent fistula, pre-existing incontinence, previous local irradiation, Crohn's disease.…”
Section: Referencesupporting
confidence: 79%
“…An internal pocket in the fistula tract remaining unhealed after infliximab treatment was suggested to be the predominant reason for recurrence [13,14]. To reach a better clinical outcome, combination treatment with infliximab and surgical intervention is highly recommended for management of Crohn's fistulae [15]. Nonetheless, even this strategy does not result in a satisfactory healing for many patients.…”
Section: Introductionmentioning
confidence: 99%
“…Another practical division considers simple and complex fistulas. Complex fistulas connected with an increased postoperative incontinence rate include the following: high transsphincteric (comprising >1/3 of the EAS diameter), suprasphincteric, retrosphincteric, rectovaginal, and horseshoe fistulas, anterior fistulas in female patients, and fistulas coexisting with Leśniowski-Crohn's or post-radiation diseases (9).…”
Section: R E V I E W P a P E R Smentioning
confidence: 99%